Using Electrical Resistivity Tomography to Understand the Hydrogeological Behavior of Acid Drainage Percolation in a Fractured Aquifer at a Uranium Mining Site - Moreira, César Augusto [UNESP]; Netto, Leonides Guireli [UNESP]; de Siqueira Buchi, Fernanda Miranda [UNESP]; Hansen, Marco Antônio Fontoura; Masquelin, Henri; Lima, José Pedro Rebés (Springer Nature, 2024)
Brazilian mining ventures aged 30 years or older were studied, revealing historical oversights in environmental planning that have caused substantial environmental liabilities during active mining and decommissioning. Electrical resistivity tomography surveys were conducted in a decommissioning uranium mine in southeast Brazil. The results provided valuable insights into local hydrogeological dynamics, revealing the flow of acid mine drainage in two distinct systems: the porous waste rock pile and the fractured underlying crystalline basement. Geo-electrical sections displayed conductive anomalies indicating hydraulic connectivity between the waste rock pile and the underlying fractured aquifer through crystalline basement fractures. This connection was substantiated by sub-vertical zones of low electrical resistivity interpreted as groundwater influx from the porous system to the fractured aquifer. Consequently, the waste rock pile acted as a localized recharge zone for the regional aquifer, facilitating chemical exchanges between the two systems. Furthermore, the study successfully differentiated less impacted saturated zones (resistivity ≈80 Ω·m) from those associated with acid mine drainage (< 40 Ω·m). Preliminary investigations identified a complex fracture network in the study area, comprising two main fault systems with preferential NE and NW orientations, nearly orthogonal to each other. This fracture network demonstrated continuity, playing a fundamental role in sustaining flow within the local and regional drainage network.